Super-high-resolution aerial imagery, digital surface models and 3D point clouds of the Northern Kitluk Coast, Alaska - Tabea Rettelbach; Ingmar Nitze; Inge Grünberg; Jennika Hammar; Simon Schäffler; Daniel Hein; Matthias Gessner; Tilman Bucher; Jörg Brauchle; Jörg Hartmann; Torsten Sachs; Julia Boike; et al. (PANGAEA, 2024)
As part of the Perma-X airborne campaign led by the Alfred Wegener Institute in 2021, we collected super-high-resolution multispectral imagery of permafrost landscapes with the Modular Aerial Camera System (MACS), developed by the German Aerospace Center. From these images, we photogrammetrically processed four-band orthophotos (blue, green, red, near-infrared) and digital surface models at very high spatial resolution of 10 cm, as well as photogrammetric point clouds in RGB and NIR. This data collection aggregates four data subsets of the northern Kitluk Coast, Alaska, covering approximately 90 km^2. All images were collected on 9 July 2021.